Electrode containing oxygen evolution electrode catalyst
By integrating manganese oxides or iridium-manganese oxides with a conductive substrate of controlled thickness, the electrode design enhances oxygen-generating electrocatalytic activity, addressing the need for improved water electrolysis efficiency and hydrogen production.
Patent Information
- Application Number
- JP2024563542
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-06-24
- Filing Date
- 2024-08-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-08-21
AI Technical Summary
Existing electrodes using manganese oxides and iridium-manganese oxides as oxygen-generating electrocatalysts require further performance improvements to meet the increasing demand for higher efficiency in water electrolysis.
The development of an electrode with an oxygen-generating electrocatalyst containing manganese oxides or iridium-manganese oxides, paired with a conductive substrate of controlled thickness between 50 μm and 500 μm, which enhances the oxygen-generating electrocatalytic activity.
The proposed electrode design achieves significantly higher oxygen-generating electrocatalytic activity compared to conventional electrodes, thereby improving the efficiency of water electrolysis and hydrogen production.
Smart Images

Figure 0007659138000001 
Figure 0007659138000002 
Figure 0007659138000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode that includes an oxygen evolving electrocatalyst that includes manganese oxide and / or iridium-manganese oxide. [Background technology]
[0002] Due to the problems of fossil fuel depletion and environmental pollution, attention is being paid to the use of hydrogen as a clean energy source and methods for producing it. Water electrolysis is one of the effective methods for producing high-purity hydrogen gas. In water electrolysis, iridium catalysts are widely known as highly active oxygen-evolving electrode catalysts (e.g., Non-Patent Document 1). However, iridium reserves are extremely small compared to other precious metals, and even if water electrolysis technology becomes widespread in the future, there will not be enough catalysts to meet the demand.
[0003] Against this background, the present inventors have reported manganese oxide (Patent Document 1) and iridium-manganese oxide (Patent Document 2), in which a small amount of iridium is introduced into manganese oxide, as oxygen evolving electrode catalysts in which the amount of iridium used is reduced compared to conventional methods. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication 2019 / 117199 [Patent Document 2] International Publication 2022 / 264960 [Non-patent literature]
[0005] [Non-Patent Document 1] F. Birol, World Energy Outlook 2016, International Energy Agency (IEA), Paris, 2016. Summary of the Invention [Problem to be solved by the invention]
[0006] Although the manganese oxide of Patent Document 1 and the iridium-manganese oxide of Patent Document 2 have high oxygen evolution electrode catalytic activity, further performance improvements are required to meet the strong demand in recent years for more efficient water electrolysis. The present disclosure aims to provide at least one of an electrode that exhibits high oxygen evolving electrode catalytic activity compared to conventional electrodes that use manganese oxide and iridium-manganese oxide (hereinafter also referred to as "manganese-based oxide") as an oxygen evolving electrode catalyst, a water electrolysis method using the electrode, and a method for producing hydrogen using the electrode. [Means for solving the problem]
[0007] In the studies of electrodes using conventional manganese oxides as oxygen generating electrode catalysts as in Patent Documents 1 and 2, no attention was paid to the structure of the conductive substrate constituting those electrodes. In the present disclosure, attention was paid to the relationship between the structure of the conductive substrate constituting the oxygen generating electrode and the catalyst. As a result, it was found that an electrode using manganese oxides as an oxygen generating electrode catalyst exhibits significantly higher oxygen generating electrode catalytic activity as an anode for an electrolytic reaction involving oxygen generation, as compared to conventional electrodes using manganese oxides as an oxygen generating electrode catalyst, by controlling the thickness of the conductive substrate.
[0008] That is, the present invention is as defined in the claims and its gist is as follows. [1] An electrode comprising: an oxygen generating electrode catalyst containing at least one of manganese oxide and iridium-manganese oxide; and a conductive substrate having a thickness of 50 μm or more and less than 500 μm. [2] The content of the oxygen generating electrode catalyst is 0.1 mg / cm per geometric area of the electrode. 2 More than 12.0mg / cm 2 The electrode according to [1] above, which is: [3] The electrode according to [1] or [2] above, wherein the oxygen evolution electrode catalyst is an iridium-manganese oxide. [4] The iridium content is 0.01 mg / cm2 per geometric area of the electrode. 2 More than 1.0mg / cm 2 The electrode according to [3] above, which is: [5] The electrode according to [3] or [4] above, wherein a molar ratio of iridium to manganese is 0.001 or more and 0.100 or less. [6] The electrode according to any one of [1] to [5], wherein the conductive base material comprises titanium. [7] A water electrolysis device comprising the electrode according to any one of [1] to [6]. [8] A method for producing hydrogen by electrolyzing water using the electrode according to any one of [1] to [6] above. Effect of the Invention
[0009] The present disclosure can provide at least one of an electrode that exhibits high oxygen evolving electrode catalytic activity compared to conventional electrodes that use a manganese-based oxide as an oxygen evolving electrode catalyst, a water electrolysis method using the electrode, and a method for producing hydrogen using the electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, one embodiment of the present disclosure will be described. The electrode of this embodiment is an electrode including an oxygen generating electrode catalyst containing at least one of manganese oxide and iridium-manganese oxide, and a conductive substrate having a thickness of 50 μm or more and less than 500 μm. The oxygen generating electrode catalyst included in the electrode of this embodiment is an oxygen generating electrode catalyst containing at least one of manganese oxide and iridium-manganese oxide (hereinafter also referred to as a "manganese-based electrode catalyst"). This allows the electrode of this embodiment to function as an oxygen generating electrode.
[0011] The manganese-based electrode catalyst preferably contains manganese oxide, more preferably contains manganese dioxide, further preferably contains manganese dioxide having a γ-, β-, ε- or α-type crystal structure, and even more preferably contains manganese dioxide having a β-type crystal structure. The crystal structure of the manganese-based electrode catalyst is preferably a single phase, but may be two or more types of manganese-based electrode catalysts having a single phase crystal structure, or may be a mixed phase having a plurality of crystal structures.
[0012] In this embodiment, the crystal structure of the manganese-based electrode catalyst can be identified by comparing its powder X-ray diffraction (hereinafter also referred to as "XRD") pattern with the XRD pattern (hereinafter also referred to as "reference pattern") registered in the Powder Diffraction File (PDF) of the International Center for Diffraction Data (ICDD). The reference patterns of manganese dioxide having a γ-type, β-type, ε-type or α-type crystal structure may be PDF No. 14-0644 (γ-type), 24-0735 (β-type), 30-0820 (ε-type) or 44-0141 (α-type), respectively.
[0013] In this embodiment, the XRD pattern may be obtained by XRD measurement using a general powder X-ray diffraction device (for example, device name: Ultima IV Protectus, manufactured by Rigaku Corporation) under the following conditions. Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 4° / min Measurement range: 2θ=10° to 80° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: D / teX Ultra Ni filter used
[0014] The XRD peak is a peak whose 2θ value at the peak top is detected in an XRD pattern analysis using general analysis software (eg, IGOR Pro 8, manufactured by WaveMetrics, or SmartLab StudioII, manufactured by Rigaku). The content of the oxygen generating electrode catalyst per geometric area of the electrode of this embodiment (hereinafter also referred to as the "catalyst content") is 0.1 mg / cm 2 More than 12.0mg / cm 2 Preferably, it is 0.5 mg / cm or less. 2 More than 11.0mg / cm 2 Less than 0.8 mg / cm is more preferable. 2 More than 10.0mg / cm 2 The following is even more preferred:
[0015] The "geometric area" is the area equivalent to the projected area without considering surface irregularities or gaps, and is the projected area of the surface (geometric surface) that faces the electrolyte membrane when constructing a membrane-electrode assembly (hereinafter also referred to as "MEA"). The "geometric area of an electrode" is the projected area of an electrode, and is the area of a plane calculated by length x width when the shape of the electrode is specified as length x width x depth.
[0016] The manganese-based electrode catalyst is preferably a catalyst containing manganese oxide and iridium (iridium-manganese oxide) because it tends to have high activity as an oxygen generating electrode catalyst. Examples of iridium-manganese oxide include iridium supported on manganese oxide and iridium dispersed on the surface of manganese oxide. The average metal valence of iridium is preferably 3.1 or more and 3.8 or less.
[0017] In an electrode using iridium-manganese oxide as an oxygen generating electrode, the iridium content per geometric area of the electrode (hereinafter also referred to as the "iridium content") is 0.001 mg / cm 2 It is preferable that the concentration is 0.005 mg / cm or more. 2 More preferably, it is 0.01 mg / cm or more. 2 More preferably, it is 0.02 mg / cm or more.2 It is particularly preferable that the iridium content is 1.0 mg / cm or more. 2 Preferably, it is 0.75 mg / cm or less. 2 More preferably, it is 0.5 mg / cm or less. 2 When the upper or lower limit of the iridium content is within this range, high oxygen evolution electrode catalytic activity is easily achieved when combined with a conductive base material described below. The iridium content is 0.001 mg / cm or less. 2 More than 1.0mg / cm 2 Below, 0.005mg / cm 2 More than 0.75mg / cm 2 Less than or equal to 0.01 mg / cm 2 More than 0.5mg / cm 2 The following is preferred:
[0018] In the iridium-manganese oxide, the molar ratio of iridium to manganese (hereinafter also referred to as "Ir / Mn molar ratio") is preferably 0.001 or more, more preferably 0.002 or more, and even more preferably 0.010 or more. The Ir / Mn molar ratio is preferably 0.100 or less, more preferably 0.075 or less, and even more preferably 0.050 or less. When the upper or lower limit of the Ir / Mn molar ratio is this value, it is easy to achieve high oxygen evolution electrode catalytic activity when combined with a conductive base material described later. The Ir / Mn molar ratio is preferably 0.001 or more and 0.100 or less, 0.002 or more and 0.075 or less, or 0.010 or more and 0.050 or less.
[0019] The electrode of this embodiment includes a conductive substrate having a thickness of 50 μm or more and less than 500 μm. In general, the thickness of the conductive substrate has little effect on the oxygen evolution electrode catalytic activity, and the current efficiency improves slightly as the conductive substrate becomes thinner (for example, S. Toghyani et al., Energy, 2018, 152, 237-246.). In contrast, in the electrode of this embodiment, the conductive substrate has a thickness of less than 500 μm, which has a remarkable effect of dramatically improving the oxygen evolution electrode catalytic activity of the manganese-based electrode catalyst.
[0020] When the thickness of the conductive substrate is less than 50 μm, the mechanical strength of the conductive substrate decreases, and the electrode becomes easily damaged. On the other hand, when the thickness of the conductive substrate is 500 μm or more, the electrical resistance of the conductive substrate increases, and as a result, the oxygen generating electrode catalytic activity decreases. In order to exhibit a better oxygen generating electrode catalytic activity, the thickness of the conductive substrate is preferably 75 μm or more, and more preferably 100 μm or more. In addition, the thickness of the conductive substrate is preferably 450 μm or less, more preferably 300 μm or less, even more preferably less than 300 μm, and particularly preferably 250 μm or less. The thickness range of the conductive substrate is preferably 50 μm or more and 450 μm or less, more preferably 75 μm or more and 300 μm or less, and even more preferably 100 μm or more and 250 μm or less.
[0021] The term "thickness" refers to the length in the direction perpendicular to the geometric surface. The term "thickness of the conductive substrate" refers to the length in the direction perpendicular to the geometric surface of the conductive substrate, and corresponds to the width of the electrode when the electrode shape is defined as length x width x depth.
[0022] The conductive substrate may be any substrate made of a conductive material, and is preferably a substrate containing titanium. The shape of the conductive substrate can be one or more selected from the group consisting of mesh, cloth, and plate, and is preferably mesh because it is likely to have high oxygen generating electrode catalytic activity.Specific conductive substrates include titanium mesh made of fibrous or powdered conductive titanium metal, and sintered titanium mesh obtained by heat treatment of the titanium mesh.These conductive substrates are preferably coated with platinum on their surfaces because they are likely to have high oxygen generating electrode catalytic activity, and the conductive substrate is preferably a platinum-coated titanium mesh, and more preferably a platinum-coated sintered titanium mesh.
[0023] The porosity of the conductive substrate is preferably 30% or more and 80% or less, more preferably 40% or more and 70% or less. Here, the porosity is defined as the volume of the space portion in the volume of the conductive substrate that is not occupied by the conductive substrate, and the porosity can be measured, for example, by mercury plethysmography. When the porosity is within the above range, excellent effects can be obtained in that the mechanical strength of the electrode is increased and water, which is a reactive gas for oxygen generation, can be smoothly supplied.
[0024] The electrode of this embodiment only needs to include a manganese-based electrode catalyst and a conductive substrate, and is preferably configured with a conductive substrate at least partially coated with the manganese-based electrode catalyst (hereinafter also referred to as a "composite electrode material"). The manganese oxide composite electrode material is a conductive substrate at least partially coated with the above-mentioned manganese oxide, and the iridium-manganese oxide composite electrode material is a conductive substrate at least partially coated with the above-mentioned iridium-manganese oxide.
[0025] Examples of the electrode structure of this embodiment include an electrode having a structure in which manganese oxide is supported on the surface of a conductive substrate, an electrode having a structure in which manganese oxide and iridium are supported on the surface of a conductive substrate, and an electrode having a structure in which manganese oxide is supported on the surface of a conductive substrate and iridium is supported on the manganese oxide.
[0026] The electrode of the present embodiment can be used as an oxygen generating electrode, and is preferably used as an oxygen generating electrode in a water electrolysis device. The electrode of the present embodiment can be used in a method for producing hydrogen by electrolysis of water.
[0027] The method for producing the electrode of this embodiment will be described below. The method for producing the electrode of the present embodiment is not particularly limited as long as it can produce an electrode having the above-described configuration. A preferred production method includes a production method including an electrolysis step of electrolytically depositing manganese oxide on a conductive base material to obtain a manganese oxide-containing base material, and a heat treatment step of heat treating the manganese oxide-containing base material.
[0028] In the electrolysis step, manganese oxide is electrolytically deposited on the conductive substrate, thereby obtaining a manganese oxide-containing substrate. As long as manganese oxide is electrolytically deposited on the surface of the conductive substrate, any method may be used for electrolytic deposition, and any method may be used as long as the conductive substrate is immersed in an electrolyte and electrolyzed.
[0029] The electrolyte may be any solution containing manganese, and the manganese concentration in the electrolyte is preferably 5 g / L or more and 50 g / L or less. The electrolyte is preferably a solution containing manganese sulfate, more preferably an aqueous manganese sulfate solution, in which the sulfuric acid concentration is preferably 5 g / L or more and 65 g / L or less, and the manganese concentration is preferably 5 g / L or more and 50 g / L or less.
[0030] The conductive substrate to be subjected to the electrolysis step may be any of the above-mentioned conductive substrates, and may have a thickness of less than 500 μm, preferably 300 μm or less, and more preferably a platinum-coated titanium mesh, or even a platinum-coated sintered titanium mesh.
[0031] In the electrolysis, the conductive substrate is immersed in the electrolyte and electrolyzed. The electrolysis conditions may be any conditions that allow electrolytic deposition of manganese oxide, and the current density is 0.3 mA / cm per geometric area of the conductive substrate. 2 More than 20mA / cm 2 and the electrolysis temperature is 93°C or higher and 98°C or lower.
[0032] In the heat treatment step, the manganese oxide-containing substrate is heat-treated. This enhances the adhesion between the manganese oxide and the conductive substrate. The heat treatment in the heat treatment step may be performed under conditions that allow the manganese oxide in the manganese oxide-containing substrate to maintain the above-mentioned crystal structure. The heat treatment atmosphere may be an air atmosphere or an inert atmosphere, or even an air atmosphere, and the heat treatment temperature may be 100°C or higher and 600°C or lower. The heat treatment time may be appropriately adjusted depending on the size of the conductive substrate to be subjected to the heat treatment, and may be, for example, 10 minutes or higher and 24 hours or lower.
[0033] When manufacturing an electrode in which the manganese-based electrode catalyst is iridium-manganese oxide, it is preferable to have a contact step of contacting the manganese oxide-containing base material with an iridium salt solution prior to the heat treatment step, whereby an iridium-manganese oxide-containing base material is obtained, and the iridium-manganese oxide-containing base material can be provided in the heat treatment step instead of the manganese oxide-containing base material.
[0034] The iridium salt solution to be subjected to the contact step may be any solution containing an iridium salt, and is preferably a solution containing an iridium salt and sulfuric acid, or more preferably an aqueous solution containing an iridium salt and sulfuric acid. Examples of the iridium salt include at least one of potassium hexachloroiridate (K2IrCl6) and hexachloroiridate (H2IrCl6). The iridium concentration of the iridium salt solution is preferably 0.001 g / L or more and 10 g / L or less.
[0035] The manganese oxide-containing substrate may be contacted with the iridium salt solution by immersing the manganese oxide-containing substrate in the iridium salt solution. The contact conditions are not particularly limited as long as the surface of the manganese oxide-containing substrate is impregnated with iridium, and examples of the contact temperature include 20° C. or higher and 100° C. or lower. The contact time may be appropriately adjusted depending on the size of the manganese oxide-containing substrate, and examples of the contact time include 30 minutes or longer and 24 hours or shorter. EXAMPLES
[0036] The present disclosure will be described in detail below with reference to examples and comparative examples, but the present disclosure is not limited to these examples. <Analysis of metal content in electrodes>
[0037] A sample electrode measuring 10 mm in length and 10 mm in width was immersed in 10 mL of a mixed solution of hydrochloric acid and nitric acid, and the oxygen generating electrode catalyst contained in the electrode was dissolved to obtain a sample solution. The composition of the sample solution was measured by inductively coupled plasma atomic emission spectrometry (ICP-AES) using a general ICP device (device name: Optima 830, manufactured by PerkinElmer). <Crystal structure identification>
[0038] An XRD pattern was obtained using a general powder X-ray diffractometer (device name: Ultima IV Protectus, manufactured by Rigaku Corporation) under the following conditions. Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 4° / min Measurement range: 2θ=10° to 80° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: D / teX Ultra Ni filter used
[0039] The crystal phase of the sample was identified by comparing the obtained XRD pattern with the XRD pattern (hereinafter also referred to as "reference pattern") registered in the PDF (Powder Diffraction File) of the ICDD (International Center for Diffraction Data). The reference patterns of manganese dioxide having γ-, β-, ε- or α-type crystal structures were PDF No. 14-0644 (γ-type), 24-0735 (β-type), 30-0820 (ε-type) or 44-0141 (α-type), respectively. <Measurement of oxygen evolution electrode catalytic activity>
[0040] Using a PEM-type water electrolysis cell in which the electrodes of the examples and comparative examples were used as the working electrodes (anodes), the oxygen evolution electrode catalytic activity was evaluated by linear sweep voltammetry (LSV) of a two-electrode system under the following conditions.
[0041] Voltage increase rate: 10mV / sec Water temperature: 80℃ Water supply rate: 2mL / min From this evaluation, the current density at a voltage of 2 V (hereinafter also simply referred to as "current density") was obtained. In addition, the ratio of the current density of the electrodes of the examples and comparative examples to the current density of an electrode having a conductive substrate with a thickness of 500 μm (hereinafter also referred to as "relative current density") was obtained.
[0042] <Manganese oxide> Example 1 The electrolytic cell was filled with a sulfuric acid-manganese sulfate mixed solution with a sulfuric acid concentration of 35 g / L and a manganese sulfate concentration of 31 g / L, and a conductive substrate made of Pt-coated Ti fiber (product name: titanium fiber sintered body 2GDL08N-020 BS05PT platinum-plated product, manufactured by Bekaert, thickness 200 μm, Pt thickness 0.5 μm, porosity 56%) was immersed in the solution. A current density of 7 mA / cm was applied to the conductive substrate. 2 A current was applied for 10 minutes at 40° C. to electrochemically deposit manganese oxide onto the conductive substrate.
[0043] The conductive substrate on which the obtained manganese oxide was electrochemically deposited was subjected to an annealing treatment in an air atmosphere at 450° C. for 5 hours to obtain a manganese oxide composite electrode material, which was used as the electrode of this example. The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (manganese oxide) having a β-type crystal structure on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and the manganese content is 1.2 mg / cm 2 (The iridium content was 0 g / cm 2 , Ir / Mn molar ratio is 0).
[0044] [Oxygen evolution electrode catalytic activity] A PEM-type water electrolysis cell was prepared using the electrode of this example as the working electrode (anode) and equipped with a membrane-electrode assembly (hereinafter also referred to as "MEA") prepared by the following method. A conductive catalyst ink was prepared by mixing a 20% by mass platinum-supported carbon catalyst (product name: 20% Platinum on Vulcan XC-72, Sigma-Aldrich) with a solution containing water, ethanol, and ionomer (product name: Nafion dispersion solution, Sigma-Aldrich). This was applied to carbon paper (product name: TGP-H-060, Toray), air-dried, and used as the counter electrode.
[0045] Next, a Nafion membrane (product name: Nafion 115, manufactured by Sigma-Aldrich) was washed and protonated by boiling in 3% by mass hydrogen peroxide for 1 hour, pure water for 1 hour, 1 M sulfuric acid aqueous solution for 1 hour, and pure water for 1 hour, in that order, to prepare an electrolyte membrane.
[0046] A sample electrode was used as the working electrode (anode), and an electrolyte membrane was sandwiched between the catalytic surfaces of the working electrode (anode) and the counter electrode. The electrolyte membrane was then heated at 135°C and a clamping force of 400 kg / cm using a hot press machine (product name: SA-302, manufactured by Tester Sangyo Co., Ltd.). 2 The MEA was obtained by hot pressing for 3 minutes at 40°C. The obtained MEA was attached to the housing of a PEM water electrolysis cell (product name: WE-4S-RICW, manufactured by FC Development Co., Ltd.) to prepare a PEM water electrolysis cell.
[0047] The obtained PEM-type water electrolysis cell was used to evaluate the oxygen evolution electrode catalytic activity.
[0048] Example 2 The electrode of this example was obtained in the same manner as in Example 1, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 300 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (manganese oxide) having a β-type crystal structure on a conductive substrate made of Pt-coated Ti fiber with a thickness of 300 μm, and the manganese content is 1.2 mg / cm2 (The iridium content was 0 g / cm 2 , Ir / Mn molar ratio is 0).
[0049] The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0050] Comparative Example 1 The electrode of this comparative example was obtained in the same manner as in Example 1, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (manganese oxide) having a β-type crystal structure on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and the manganese content is 1.2 mg / cm 2 (The iridium content was 0 g / cm 2 , Ir / Mn molar ratio is 0). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0051] The following table shows the evaluation results of Examples 1 and 2 and Comparative Example 1. The current density in the table is the value at a voltage of 2V.
[0052] [Table 1]
[0053] Example 3 The electrode of this example was obtained in the same manner as in Example 1, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 200 μm, Pt thickness of 0.5 μm, and porosity of 56% was used as the conductive base material, and the current application time was set to 20 minutes. The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (manganese oxide) having a β-type crystal structure on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and the manganese content is 2.4 mg / cm 2 (The iridium content was 0 g / cm 2 , Ir / Mn molar ratio is 0). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0054] Comparative Example 2 The electrode of this comparative example was obtained in the same manner as in Example 3, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (manganese oxide) having a β-type crystal structure on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and the manganese content is 2.4 mg / cm 2 (The iridium content was 0 g / cm 2 , Ir / Mn molar ratio is 0). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0055] The following table shows the evaluation results of Example 3 and Comparative Example 2. The current density in the table is the value at a voltage of 2V.
[0056] [Table 2]
[0057] Example 4 The electrode of this example was obtained in the same manner as in Example 3, except that the current application time was 5 minutes. The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (manganese oxide) having a β-type crystal structure on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and the manganese content is 0.6 mg / cm 2 (The iridium content was 0 g / cm 2 , Ir / Mn molar ratio is 0). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0058] Comparative Example 3 The electrode of this comparative example was obtained in the same manner as in Example 4, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (manganese oxide) having a β-type crystal structure on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and the manganese content is 0.6 mg / cm 2 (The iridium content was 0 g / cm 2 , Ir / Mn molar ratio is 0). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0059] The following table shows the evaluation results of Example 4 and Comparative Example 3. The current density in the table is the value at a voltage of 2V.
[0060] [Table 3]
[0061] It was confirmed that the electrode using manganese oxide as the oxygen generating electrode catalyst has a significantly improved oxygen generating electrode catalytic activity compared to a conventional electrode (with a conductive substrate thickness of 500 μm) using manganese oxide as the oxygen generating electrode catalyst, due to the reduced thickness of the conductive substrate.
[0062] <Iridium-manganese oxide> Example 5 A manganese oxide composite electrode material was obtained in the same manner as in Example 1, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 200 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. Next, the manganese oxide composite electrode material was immersed in an iridium salt solution of 0.05 g / L potassium hexachloroiridate (K2IrCl6) and 0.5 g / L sulfuric acid at 95°C for 168 hours, and then annealed in air at 450°C for 5 hours to obtain an iridium-manganese oxide composite electrode material, which was used as the electrode of this example. The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and the manganese content is 1.2 mg / cm 2 and iridium content is 0.20 mg / cm 2 (Ir / Mn molar ratio was 0.048). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0063] Comparative Example 4 The electrode of this comparative example was obtained in the same manner as in Example 5, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and the manganese content is 1.2 mg / cm 2 and iridium content is 0.20 mg / cm 2 (Ir / Mn molar ratio was 0.048). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0064] The following table shows the evaluation results of Example 5 and Comparative Example 4. The current density in the table is the value at a voltage of 2V.
[0065] [Table 4]
[0066] Example 6 A manganese oxide composite electrode material was obtained in the same manner as in Example 1, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 100 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. Next, an electrode of this example was obtained in the same manner as in Example 5, except that the K2IrCl6 concentration in the iridium salt solution was set to 0.02 g / L and the manganese oxide composite electrode material was immersed in the iridium salt solution for 24 hours.
[0067] The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 100 μm, and the manganese content is 1.2 mg / cm 2 and iridium content is 0.10 mg / cm 2 (Ir / Mn molar ratio was 0.024). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0068] Example 7 The electrode of this example was obtained in the same manner as in Example 6, except that Pt-coated Ti fiber (product name: titanium fiber sintered body 2GDL08N-020 BS05PT platinum-plated product, manufactured by Bekaert, thickness 200 μm, Pt thickness 0.5 μm, porosity 56%) was used as the conductive substrate.
[0069] The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and the manganese content is 1.2 mg / cm 2 and iridium content is 0.10 mg / cm 2 (Ir / Mn molar ratio was 0.024). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0070] Example 8 The electrode of this example was obtained in the same manner as in Example 6, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 300 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material.
[0071] The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 300 μm, and the manganese content is 1.2 mg / cm 2 and iridium content is 0.10 mg / cm 2 (Ir / Mn molar ratio was 0.024). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0072] Comparative Example 5 The electrode of this comparative example was obtained in the same manner as in Example 6, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and the manganese content is 1.2 mg / cm 2 and iridium content is 0.10 mg / cm 2 (Ir / Mn molar ratio was 0.024). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0073] The following table shows the evaluation results of Examples 6 to 8 and Comparative Example 5. The current density in the table is the value at a voltage of 2V.
[0074] [Table 5]
[0075] Example 9 The electrode of this example was obtained in the same manner as in Example 7, except that the K2IrCl6 concentration in the iridium salt solution was 0.01 g / L. The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and the manganese content is 1.2 mg / cm 2 and iridium content is 0.01 mg / cm 2 (Ir / Mn molar ratio was 0.002). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0076] Comparative Example 6 The electrode of this comparative example was obtained in the same manner as in Example 9, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and the manganese content is 1.2 mg / cm 2 and iridium content is 0.01 mg / cm 2 (Ir / Mn molar ratio was 0.002). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode). The following table shows the evaluation results of Example 9 and Comparative Example 6. The current density in the table is the value at a voltage of 2V.
[0077] [Table 6]
[0078] Example 10 A manganese oxide composite electrode material was obtained in the same manner as in Example 3. Next, an electrode of this example was obtained in the same manner as in Example 7, except that the manganese oxide composite electrode material was used. The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and the manganese content is 2.4 mg / cm 2 and iridium content is 0.10 mg / cm 2 (Ir / Mn molar ratio was 0.012). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0079] Comparative Example 7 The electrode of this comparative example was obtained in the same manner as in Example 10, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive substrate. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and the manganese content is 2.4 mg / cm 2 and iridium content is 0.10 mg / cm 2 (Ir / Mn molar ratio was 0.012). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0080] The following table shows the evaluation results of Example 10 and Comparative Example 7. The current density in the table is the value at a voltage of 2V.
[0081] [Table 7]
[0082] Example 11 A manganese oxide composite electrode material was obtained in the same manner as in Example 4. Next, an electrode of this example was obtained in the same manner as in Example 7, except that the manganese oxide composite electrode material was used. The electrode of this example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and the manganese content is 0.6 mg / cm 2 and iridium content is 0.05 mg / cm 2 (Ir / Mn molar ratio was 0.024). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this example was used as the working electrode (anode).
[0083] Comparative Example 8 The electrode of this comparative example was obtained in the same manner as in Example 11, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of manganese dioxide (iridium-manganese oxide) having a β-type crystal structure and carrying iridium on its surface, on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and the manganese content is 0.6 mg / cm 2 and iridium content is 0.05 mg / cm 2 (Ir / Mn molar ratio was 0.024). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0084] The following table shows the evaluation results of Example 11 and Comparative Example 8. The current density in the table is the value at a voltage of 2V.
[0085] [Table 8]
[0086] It was confirmed that the electrode using iridium-manganese oxide as the oxygen generating electrode catalyst has significantly improved oxygen generating electrode catalytic activity compared to a conventional electrode (with a conductive substrate thickness of 500 μm) using iridium-manganese oxide as the oxygen generating electrode catalyst, due to the reduced thickness of the conductive substrate.
[0087] <Iridium oxide> Comparative Example 9 A conductive catalyst ink containing 4.7 g / L of iridium oxide was prepared by mixing commercially available iridium oxide powder (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with pure water, and this was applied to a conductive substrate consisting of Pt-coated Ti fiber (product name: titanium fiber sintered body 2GDL08N-020 BS05PT platinum-plated product, manufactured by Bekaert, thickness 200 μm, Pt thickness 0.5 μm, porosity 56%), and air-dried. The obtained conductive substrate containing iridium oxide was subjected to annealing treatment in an air atmosphere at 450° C. for 5 hours to obtain an iridium oxide composite electrode material, which was used as the electrode of this comparative example.
[0088] The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of iridium oxide on a conductive substrate made of Pt-coated Ti fiber with a thickness of 200 μm, and has an iridium content of 0.1 mg / cm 2 (manganese content was 0 g / cm 2 , Ir / Mn molar ratio is ∞). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0089] Comparative Example 10 The electrode of this comparative example was obtained in the same manner as in Comparative Example 9, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 300 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of iridium oxide on a conductive substrate made of Pt-coated Ti fiber with a thickness of 300 μm, and has an iridium content of 0.1 mg / cm 2 (manganese content was 0 g / cm 2 , Ir / Mn molar ratio is ∞).
[0090] The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0091] Comparative Example 11 The electrode of this comparative example was obtained in the same manner as in Comparative Example 9, except that a Pt-coated Ti fiber (product name: Pt-plated Ti fiber sintered body, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) with a thickness of 500 μm, a Pt thickness of 0.5 μm, and a porosity of 56% was used as the conductive base material. The electrode of this comparative example is an electrode having an oxygen generating electrode catalyst made of iridium oxide on a conductive substrate made of Pt-coated Ti fiber with a thickness of 500 μm, and has an iridium content of 0.1 mg / cm 2(manganese content was 0 g / cm 2 , Ir / Mn molar ratio is ∞). The oxygen evolution electrode catalytic activity was evaluated in the same manner as in Example 1, except that the electrode of this comparative example was used as the working electrode (anode).
[0092] The evaluation results of Comparative Examples 9 to 11 are shown in the table below. Note that the current density in the table below is the value at a voltage of 2V.
[0093] [Table 9]
[0094] In the electrode using iridium oxide as the oxygen evolution electrode catalyst, even if the thickness of the conductive substrate was reduced, the change in the oxygen evolution electrode catalytic activity was small.
[0095] From the above results, it was confirmed that the significant improvement in oxygen evolution electrode catalytic activity due to a reduction in the thickness of the conductive substrate is a behavior unique to manganese oxide and iridium-manganese oxide. The entire contents of the specification, claims and abstract of Japanese Patent Application No. 2023-135670, filed on August 23, 2023, and the entire contents of the specification, claims and abstract of Japanese Patent Application No. 2024-100953, filed on June 24, 2024, are hereby incorporated by reference as the disclosure of the specification of the present disclosure.
Claims
1. An electrode comprising an oxygen generating electrode catalyst containing at least one of manganese oxide and iridium-manganese oxide, and a conductive substrate having a thickness of 50 μm or more and less than 500 μm, wherein the content of the oxygen generating electrode catalyst per geometric area of the electrode is 0.1 mg / cm 2 12.0mg / cm or more 2 The electrodes are as follows:
2. The electrode of claim 1, wherein the oxygen evolution electrocatalyst is iridium-manganese oxide.
3. The iridium content is 0.01 mg / cm2 per geometric area of the electrode. 2 1.0mg / cm or more 2 3. The electrode of claim 2, wherein:
4. 4. The electrode according to claim 2, wherein the molar ratio of iridium to manganese is 0.001 or more and 0.100 or less.
5. 3. The electrode of claim 1 or 2, wherein the conductive substrate comprises titanium.
6. A water electrolysis device comprising the electrode according to claim 1 or 2.
7. A method for producing hydrogen by electrolysis of water using the electrode according to claim 1 or 2.
Citation Information
Patent Citations
JP1971003411A
Electrode having outer coating for carrying out electrolytic method and protecting intermediate coating on electroconductive substrate and preparation thereof
JP1982073192A
Iridium-manganese oxide composite material, iridium-manganese oxide composite electrode material, and methods for producing same
WO2022264960A1
Manganese oxide for water decomposition catalysts, manganese oxide-carbon mixture, manganese oxide composite electrode material, and respective methods for producing these materials
WO2019117199A1
Cited By
Electrolyte membrane with catalyst layer, water electrolysis cell, and water electrolysis cell stack
JP2026122445A